PENGARUH MODEL PEMBELAJARAN CARD SORT TERHADAP PEMAHAMAN PROSES FOTOSINTESIS MATA PELAJARAN IPAS KELAS IV DI SD NEGERI BALONGBESUK JOMBANG - Faizatuz Zahra; Evi Rizqi Salamah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research aims to explain the influence of the Card Sort learning model on the understanding of the photosynthesis process in Natural and Social Sciences (IPAS) subjects in class IV students at SD Negeri Balongbesuk, Jombang. The background to this research is based on students' difficulties in understanding the concept of photosynthesis due to the use of less interactive learning methods. The Card Sort learning model is expected to increase student involvement in the learning process by arranging and grouping information in the form of cards, so that they can understand concepts more systematically and have fun. This research uses a quantitative approach with a pre-test and post-test experimental design on one group of subjects.The research results showed that there was an increase in students' understanding after implementing the Card Sort learning model. This is indicated by the significant difference between the pre-test and post-test results, which were analyzed using statistical tests. The Card Sort model is proven to help students understand the concept of photosynthesis in more depth, because they can actively participate in learning and connect information more effectively. Apart from that, the interaction between students in this activity also contributes to increasing their understanding of the photosynthesis process material.Based on research findings, it is recommended that teachers apply the Card Sort learning model in science learning, especially in topics that require understanding of complex concepts such as photosynthesis. The application of this model can be used as an alternative strategy to improve student learning outcomes at the elementary school level. In addition, this research also provides recommendations for further research to explore the effectiveness of this method in various other subjects.